The effectiveness of lumbar stabilisation exercises on pain and functional disability among patients with non-specific low back pain: a systematic review - Dar, Shahid Mohd; Shamsul Muhardzi, Naim Muzaffar; Kamsan, Siti Salwana (IIUM Journal of Orofacial and Health Sciences, 2025)
Core stability exercises have emerged as a crucial intervention for managing and preventing back pain, a pervasive condition affecting millions globally. Back pain frequently arises and persists due to deficiencies or imbalances in core muscles. As a result, engaging in targeted core-strengthening exercises is thought to not only reduce pain but also greatly boost functional capabilities and improve overall quality of life. A systematic search of electronic databases (PubMed, ScienceDirect, and PEDro) was conducted to find experimental studies focusing on the impact of core stability exercises on back pain and functional independence in adults with nonspecific back pain. Out of 250 identified studies, 228 titles and abstracts were reviewed, resulting in the exclusion of 122. Among the remaining 106 articles, 93 full texts were retrieved and evaluated for eligibility. Ultimately, 8 studies met the criteria and were included in the review. Out of the eight studies, two reported no improvement in pain reduction compared to control groups. For disability, six studies assessed the outcome, of which three reported no improvement compared to control groups. The remaining studies demonstrated greater effectiveness of core stability exercises in reducing both pain and disability. These findings highlight the importance of incorporating core stability exercises into treatment plans for NSLBP and emphasize the need for tailored exercise programs to optimize outcomes.